Disseminated Gonococcal Infection Complicated by Prosthetic Joint Infection: Case Report and Genomic and Phylogenetic Analysis. (18th December 2020) - Ogbebor, Osakpolor; Mortimer, Tatum D; Fryling, Kyra; Zhang, Jessica J; Bhanot, Nitin; Grad, Yonatan H
Abstract: Neisseria gonorrhoeae infections have been increasing globally, with prevalence rising across age groups. In this study, we report a case of disseminated gonococcal infection (DGI) involving a prosthetic joint, and we use whole-genome sequencing to characterize resistance genes, putative virulence factors, and the phylogenetic lineage of the infecting isolate. We review the literature on sequence-based prediction of antibiotic resistance and factors that contribute to risk for DGI. We argue for routine sequencing and reporting of invasive gonococcal infections to aid in determining whether an invasive gonococcal infection is sporadic or part of an outbreak and to accelerate understanding of the genetic features of N gonorrhoeae that contribute to pathogenesis.